Gloucester Cathedral
The Norman Building, whose columns can here be seen within the choir triforium, was caged with a network of masonry running in vertical lines from floor to roof. The Norman apse was pulled down and replaced with a great transom window, and the whole of the choir and transepts was raised in height to allow the insertion of more clerestory light.